Feasible laser parameter in fabrication of MEMS structure on PMMA - Loh, Simon Hock Hua (2010)
Micro electromechanical systems (MEMS) fabrication leads to new requirements in production technology as the demands of high performance, small size and low cost devices are increasing. This research was conducted using a solid state pulsed Nd:YAG laser machine with a 3-axis motion controller to generate MEMS structure on PMMA. The MEMS structure generated on PMMA includes laser lines and laser spots. The effects of various laser parameters on the PMMA specimen were studied and measured under optical microscope before transferring the data to STATISTICA software for analysis. From the results, the feasible laser parameter combinations can be determined to generate the smallest possible micro feature on PMMA. Pulse energy and cutting speed from the process parameters show significant response to the line width for generation of laser lines geometry. As for the generation of laser spots geometry, pulse width from the process parameters significantly affects the diameter length of the spots. The usage of assist gas has generally decreases the laser spots diameter for generation of both micro-holes and line width for generation of micro-lines but it also causes inconsistency to the cutting quality of the laser machine. The feasible parameters for structuring laser lines (micro-channels) geometry without assist gas are found to be in the range of 40 – 90 mm/min for traverse speed and 0.01 - 0.02 J for pulse energy. On the other hand, the feasible parameters for laser lines geometry with assist gas are found to in the range of 80 - 120 mm/min for traverse speed and 0.01 – 0.02 J for pulse energy. As for structuring laser spots (micro-holes), the feasible parameters for generating laser spots geometry without assist gas are found to be in the range of 18 – 26 % for pulse height and 0.15 – 0.21 ms for pulse width. On the other hand, the feasible parameters for laser spots geometry with assist gas are found to be in the range of 24 – 36 % for pulse height and 0.15 – 0.20 ms for pulse width.